Corrosion Behavior of Zinc–Nickel and Graphene Layered Structures on Steel Substrates. Issue 3 (2nd January 2019) - Polizos, Georgios; Stehle, Yijing Y.; Sharma, Jaswinder; Voylov, Dmitry; Vlassiouk, Ivan; Shin, Seungha; Meyer, Harry M.
Abstract : Large‐area single layers of graphene are synthesized using chemical vapor deposition techniques and are assembled onto steel substrates that are finished with a thin layer of electrodeposited zinc–nickel (ZnNi). Atomic force microscopy combined with Raman spectroscopy is used to determine the number of the assembled graphene layers and to characterize the defects in their crystal structure. The graphene‐ZnNi‐steel layered specimens are exposed to a salt‐fog environment. The defects in the structure of the graphene single layers are found to accelerate corrosion and the formation of a resistive oxide layer. The chemical composition and element map of the reacted surfaces are studied by x‐ray photoelectron spectroscopy. The electrical properties of the samples before and after the salt‐fog testing are evaluated using sheet resistance measurements. Abstract : The corrosion resistance of large‐area graphene is being investigated. Three single layers of graphene are assembled onto steel substrates that are finished with a thin layer of electrodeposited zinc–nickel. The defects in the structure of the graphene single layers accelerate corrosion and the formation of a resistive oxide layer.